If Looks Could Heal: Child Health and Paternal Investment - Marlon R. Tracey; Solomon Polachek (Institute of Labor Economics (IZA), 2017)
Data from the first two waves of the Fragile Family and Child Wellbeing study indicate that infants who look like their father at birth are healthier one year later. The reason is such father-child resemblance induces a father to spend more time engaged in positive parenting. An extra day (per month) of time-investment by a typical visiting father enhances child health by just over 10% of a standard deviation. This estimate is not biased by the effect of child health on father-involvement or omitted maternal ability, thereby eliminating endogeneity biases that plague existing studies. The result has implications regarding the role of a father's time in enhancing child health, especially in fragile families.
Keywords: I12; J12; J13; 330; child health; nonresident father; father-child resemblance